4-Hydrazinoquinazoline acting as a reactive matrix for the rapid and sensitive analysis of neutral and sialylated glycans using MALDI MS. Issue 22 (5th October 2021) - Ling, Ling; Yu, Shaoning; Ding, Chuanfan
Abstract : A reactive MALDI matrix 4-hydrazinoquinazoline was used for the enhanced detection of both neutral and sialylated glycans via the dried-droplet method. Abstract : The direct analysis of glycans by matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) presents limited sensitivity due to the lower ionization efficiency of glycans. Various chemical derivatization methods have been developed to improve the detection sensitivity of glycans, but most of them need tedious preparation and cleanup procedures. Herein, a reactive matrix, 4-hydrazinoquinazoline (4-HQ), was developed for the rapid and sensitive detection of both neutral and sialylated glycans by MALDI MS. With 4-HQ as the reactive matrix, the detection limits of maltoheptaose and A3 glycan decreased 100-fold and 20-fold, respectively, compared with the conventional matrix. Moreover, 4-HQ formed homogeneous crystals and therefore showed good shot-to-shot reproducibility. Finally, the reactive matrix was successfully applied for the analysis of glycans released from glycoproteins and human serum. Importantly, the application of 4-HQ is the same as that of a conventional matrix with the additional advantage of on-target reaction at room temperature. Thus, 4-HQ can be used for the routine analysis of glycans by MALDI MS due to its simple use, great reproducibility, and enhanced detection of both neutral and sialylated glycans.